2005
DOI: 10.1590/s1516-89132005000600019
|View full text |Cite
|
Sign up to set email alerts
|

Structure of molluscan assemblages in sheltered intertidal unconsolidated environments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
0
14
1
5
Order By: Relevance
“…Seasonal dynamics of water masses in the channel greatly influences the marine biota (Migotto et al 2001). Some localities contain a wide range of sediment sizes from sand and gravel grain classes to silt or clay, and this heterogeneity has been related to abundance of bivalves (Denadai et al 2005). Araçá Bay, Engenho D'água and Velho Barreiro beaches have these heterogeneous sediments and favorable water currents.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal dynamics of water masses in the channel greatly influences the marine biota (Migotto et al 2001). Some localities contain a wide range of sediment sizes from sand and gravel grain classes to silt or clay, and this heterogeneity has been related to abundance of bivalves (Denadai et al 2005). Araçá Bay, Engenho D'água and Velho Barreiro beaches have these heterogeneous sediments and favorable water currents.…”
Section: Discussionmentioning
confidence: 99%
“…This may result from the high density of the bivalve Tivela mactroides in the area (DENADAI et al, 2005), although the siphons could not be identified to species level. According to SOARES et al (1993), whitemouth croaker has taste buds in the mentonian barbels, which makes it possible for them to perceive low-motility prey such as bivalves.…”
Section: Discussionmentioning
confidence: 97%
“…Citação bibliográfica e/ou Coleção Científica Localidadetipo Araçá Abra lioica (Dall, 1881) Migotto et al 1993;Belúcio, 1992Belúcio, , 1995Belúcio & Morgado, 1994Arruda & Amaral, 2003;Arruda et al 2003;Denadai et al 2005 Anadara notabilis (Röding, 1798) Ditadi, 1982b -Anomalocardia brasiliana (Gmelin, 1791) Leonel, 1981;Ditadi, 1982b;Montouchet, 1988;Belúcio & Morgado, 1991Migotto et al 1993;Belúcio, 1992Belúcio, , 1995Dworschak & Rodrigues, 1997;Arruda & Amaral, 1998 Montouchet, 1988;Belúcio & Morgado, 1991Duarte, 1980b;Belúcio, 1992Belúcio, , 1995 Lopes, 1993;Amaral et al 1994Amaral et al , 2003Reis et al 1996;Omena& Amaral, 1997;Reis & Amaral, 1998;Padovanni, 2009 Sawaya, & Freitas, 1972;Ditadi, 1982b;Zinner & Vani, 1986;Vani, 1987;Dworschak & Rodrigues, 1997;Anker et al 2005 (como Chaetopterus variopedatus) Chrysopetalum occidentale Johnson, 1897 Morgado, 1980b;Morgado & Amaral, 1981b;Morgado & Tanaka, 2001 (como Chaetopterus variopedatus) Cirriformia filigera (Delle Chiaje, 1825) Duarte, 1980b;…”
Section: Táxon Superior Espécieunclassified
“…Kihara & Rocha, 1993-Callinectes danae Smith, 1869Lacerda, 1981Mossolin, 1994;Caprara & Freitas, 1996;Lowenthal et al 1996;Nucci, 1998;Genofre et al 2000;Nucci et al 2001;Turra & Leite, 2005;Padovanni, 2009-Callinectes ornatus Ordway, 1863Nucci, 1998Nucci et al 2001;Gorni & Weber, 2004-Clibanarius antillensis Stimpson, 1862Garcia, 1979Brossi-Garcia & Hebling, 1983;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995Leite et al , 1996Nalesso et al 1995;, 20022004Turra et al , 1999Turra et al , 2000Barata et al 1996;Castelo-Branco et al 1996;Jacobucci & Leite, 1996;Turra & Denadai, 2001, 2002, 2004Souza, 2003;Turra, 2003Turra, , 2004Turra, , 2005 Clibanarius sclopetarius (Herbst,1796) Brossi- Garcia, 1987;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995...…”
Section: Táxon Superior Espéciementioning
confidence: 99%
See 1 more Smart Citation